النهاية غير الطبيعية للصفقات العمومية في ظل المرسوم الرئاسي 15/247 - غربي آسية - مقران هدى (جامعة المسيلة, 2022)
الصفقة العمومية مثل باقي العقود الإدارية تبرم ثم تنتهي إما طبيعيا أو نهاية غير طبيعية، وهو موضوع دراستنا نظرا لأهميتها، حيث تعددت السلطات الممنوحة للمصلحة المتعاقدة منها سلطة الإشراف والتعديل والرقابة وسلطة توقيع الجزاء وسلطة إنهاء العقد. وتكمن النهاية الغير الطبيعية في الفسخ الذي يعتبر إجراء قانوني يتم من خلاله التحرر من الرابطة العقدية جراء الإخلال بالالتزامات، وهو أخطر السلطات التي تمنح للمصلحة المتعاقدة في مواجهة المتعامل المتعاقد في عقود الصفقات العمومية، وقد تحددت صور الفسخ فهنالك حالات الفسخ الإرادة المنفردة، تتمثل في الفسخ الاتفاقي والإداري وحالات الفسخ بالإرادة غير المنفردة وهي الفسخ القضائي وبقوة القانون، كل هذه الصور لها شروط وآثار على المتعامل ولها أحكام تنظمها وفق المرسوم الرئاسي 15-247. الكلمات المفتاحية: فسخ - صفقة عمومية- جزاء - Summary The public deal, like the rest of the administrative contracts, is concluded and then ends either naturally or an abnormal end, which is the subject of our study due to its importance, as there are many powers granted to the contracting interest, including the authority to supervise, amend and control, the authority to sign the penalty and the authority to terminate the contract. The unnatural end lies in the annulment, which is a legal procedure through which freedom from the contractual bond is achieved due to a breach of obligations, and it is the most dangerous authority granted to the contracting interest in the face of the contracting dealer in public deals contracts, and the forms of annulment have been determined. Consensual, administrative, and cases of termination by non-unilateral will, which are judicial termination and by force of law, all of these forms have conditions and effects on the client and have provisions regulating them according to Presidential Decree 15-247. Keywords: annulment - public bargain - penalty -
Keywords: فسخ - صفقة عمومية- جزاء